Syagrus romanzoffiana (Cham.) Glass. PALM FRUIT ENERGY CAPACITY - Weirich Neto, Pedro Henrique; Delalibera, Hevandro Colonhese; Souza, Nátali Maidl; Martini, Jhonny; Gomes, Jaime Alberti (ENERGIA NA AGRICULTURA, 2020)
Syagrus romanzoffiana (Cham.) Glass. PALM FRUIT ENERGY CAPACITY PEDRO HENRIQUE WEIRICH NETO1, HEVANDRO COLONHESE DELALIBERA2, NÁTALI MAIDL DE SOUZA3, JHONNY MARTINI4, JAIME ALBERTI GOMES5 1 Laboratório de Mecanização Agrícola, Universidade Estadual de Ponta Grossa, Av. Carlos Cavalcanti, 4748, Campus Uvaranas, CEP 84030-900, Ponta Grossa, Paraná, Brasil, lama1@uepg.br 2 Instituto de Desenvolvimento Rural do Paraná (IDR - PR), Rodovia Celso Garcia Cid, km 375, CEP 86047-902, Londrina, Paraná, Brasil, hevandro@idr.pr.gov.br 3 Laboratório de Mecanização Agrícola, Universidade Estadual de Ponta Grossa, Av. Carlos Cavalcanti, 4748, Campus Uvaranas, CEP 84030-900, Ponta Grossa, Paraná, Brasil, natalimaidl@uepg.br 4 Laboratório de Mecanização Agrícola, Universidade Estadual de Ponta Grossa, Av. Carlos Cavalcanti, 4748, Campus Uvaranas, CEP 84030-900, Ponta Grossa, Paraná, Brasil, jhonny_martini@hotmail.com 5 Laboratório de Mecanização Agrícola, Universidade Estadual de Ponta Grossa, Av. Carlos Cavalcanti, 4748, Campus Uvaranas, CEP 84030-900, Ponta Grossa, Paraná, Brasil, jagomes@uepg.br ABSTRACT: The demand for energy and natural resources conservation results in disputes, concerns and studies. In an attempt to respond to both areas a study was developed aiming at characterizing the energy capacity of native palm tree jerivá [Syagrus romanzoffiana (Cham). Glass]. Four plants of this species were evaluated. The aspects investigated were fruit yield and potential for lipid and ethanol production. The fruit average yield potential was 41,829 kg ha-1, 24,930 kg ha-1 pulp (59.6% of the fruit) and 2,593 kg ha-1 almond (6.2% of the fruit). These contents can provide 1,641 kg ha-1 of lipid (62.2% of the almond) and 1,819 kg ha-1 of ethanol (7.3% of the pulp). The species Syagrus romanzoffiana even without any selection or genetic improvement processes, correction of soil acidity or fertility, showed high potential to be used in lipid production (almond) and ethanol (pulp). Keywords: vegetable oil, storage lipid, ethanol, alcohol, renewable energy. POTENCIAL ENERGÉTICO DO FRUTO DA PALMEIRA Syagrus romanzoffiana (Cham.) Glass RESUMO: a demanda por energia e a conservação dos recursos naturais estimulam disputas, preocupações e estudos. Tentando “transitar” nas duas áreas objetiva-se caracterizar o potencial energético da palmeira nativa jerivá [Syagrus romanzoffiana (Cham). Glass]. Foram avaliadas quatro plantas. Determinou-se produtividade, potencial para produção de lipídio e de etanol do fruto. O potencial produtivo médio de frutos é 41.829 kg ha-1, 24.930 kg ha-1 de polpa (59,6% do fruto) e 2.593 kg ha-1 de amêndoa (6,2% do fruto). Esses conteúdos podem proporcionar 1.641 kg ha-1 de lipídio (62,2% da amêndoa) e 1.819 kg ha-1 de etanol (7,3% da polpa). A espécie potencial Syagrus romanzoffiana mesmo sem passar por processos de seleção e melhoramento genético, correção de acidez e fertilidade do solo apresenta elevado potencial de uso na produção de lipídio (amêndoa) e de etanol (polpa). Palavras-chave: óleo vegetal, lipídio de reserva, etanol, álcool, energia renovável.